PERAN INTERNATIONAL LABOUR ORGANIZATION (ILO) DALAM MELINDUNGI PEKERJA ANAK DI THAILAND TAHUN 2010-2014 - Marpaung, Junpa; Tjarsono, Idjang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to explain the role of international labour organization (ILO) against child labour in thailand in 2010-2014. Thailand is one of the transit countries, source, and destination for child labor internationally. This condition causes the Thai government began to realize the urgency of the dangers of child labor. The development of anti-trafficking level Thai government intensively conducted since 2006. However, since 2006 anyway, Thailand experienced a significant increase in child labor. This research was designed to investigate the causes of the increasing cases of child labor in Thailand along the Thai government increased efforts in combating child labor.The method of data collecting is done by collecting secunder data, then analyzed in qualitative to obtain the draft about the main problem by using deductive method. The method of this research is the method of qualitative descriptive. The data is obtained through secunder data such as, book, journal, magazine, newspaper and website.International Labor Organization (ILO) focuses on eliminating the problem of child labor with the problem formulation, ILO used cultural and economic factors as the main causes of child labor. In cultural factors, there is the view that the way of life of indigenous communities and beliefs both put women under men. This ultimately has implications for the emergence of child labor. While economic factors are based on the factors of poverty, unemployment led to the migration flows have implications for the emergence of crime background material, then put forward the argument that child labor can occur because of the assumption that child labor as a reasonable step to make ends meet. The existence of migration flows in Thailand with hopes of finding a better life also make things worse.Keywords: ILO, Thailand, Child Labor, Cultural factor, Economy factor